Prosthetic management of posttraumatic external auditory canal atresia: A rare cause of conductive hearing loss - A R Adhershitha; S Anilkumar; C Rajesh; Deepak C Mohan (Wolters Kluwer Medknow Publications, 2016)
Acquired external auditory canal (EAC) atresia is an infrequent entity which can originate from a number of different causes including trauma, infection, neoplasia, inflammation, and radiotherapy. Posttraumatic atresias are exceptionally rare, only 10% of atresias are attributed to trauma in most of the series. The management of stenosis of the EAC is challenging as it is associated with residual hearing loss and late recurrence. Traditional stents often occlude the EAC, resulting in a temporary conductive hearing loss. This case report describes the technique of fabrication of a wide-bored acrylic stent which attained additional retention from the folds of the auricle. The customized earmold stent effectively prevented restenosis, while the large bore provided ventilation and improved hearing subjectively during the stenting period.